2019
DOI: 10.18510/hssr.2019.7481
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Islamic Social Reporting Index on Islamic Banking Financial Performance in Indonesia

Abstract: Purpose of this study: This study was conducted to analyze the factors that affect the disclosure of Islamic Social Reporting (ISR) in Islamic Banking on the stock exchange and analyze the data carried out on the annual report of six Islamic banks in 2013-2017. The results of this study are expected to facilitate the Islamic banks to apply the principle of full disclosure with Islam in a more comprehensive way. Methodology: The sampling technique used is sampling considerations obtained with a total samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
0
7
1
Order By: Relevance
“…Business is regulated by the "Halal-Haram code" (Quran terms where " halal means "lawful"," "acceptable", "permissible", "permitted", and "haram" means "illegal", "forbidden") [18], and compliance with the "adl" (justice) principle [19]. Due to these guidelines, a number of researchers qualify Islamic banking (accounting) as social accounting [20, p. 927], [21]. Islamic accounting, unlike Western accounting, is believed to serve a larger group of stakeholders, since it is associated with the interests of society as a whole, and does not serve the interests of certain groups [22, p. 2].…”
Section: Theoretical Aspects Of Islamic Banking As An Institutionmentioning
confidence: 99%
“…Business is regulated by the "Halal-Haram code" (Quran terms where " halal means "lawful"," "acceptable", "permissible", "permitted", and "haram" means "illegal", "forbidden") [18], and compliance with the "adl" (justice) principle [19]. Due to these guidelines, a number of researchers qualify Islamic banking (accounting) as social accounting [20, p. 927], [21]. Islamic accounting, unlike Western accounting, is believed to serve a larger group of stakeholders, since it is associated with the interests of society as a whole, and does not serve the interests of certain groups [22, p. 2].…”
Section: Theoretical Aspects Of Islamic Banking As An Institutionmentioning
confidence: 99%
“…According to the World Business Council on Sustainable Development (WBCSD), corporate social responsibility constitutes corporate commitment to maintain ethics in behavior and contributes to the sustainable economic development (Effendi, 2009;Putri et al, 2019). Elkington (1997) conveys that reporting system discloses corporate social responsibility (CSR) information as the triple bottom line reporting or the report which discloses the information about the corporate social, environmental, and economic performance.…”
Section: Disclosure Of Corporate Social Responsibility and Islamic Social Reportingmentioning
confidence: 99%
“…However, the research did not provide comprehensive analysis about the ISR index, because it focused on its relationship with financial performance. Another previous research from Putri et al, (2019) analyzed factors that affected ISR in six Islamic banks on the stock exchange with 48 index points of ISR. This research concluded that on average from 2013 to 2017, the highest score of ISR index was obtained by Bank Muamalat Indonesia and there was no influence from profitability and leverage to ISR index (Putri et al, 2019).…”
Section: Disclosure Of Corporate Social Responsibility and Islamic Social Reportingmentioning
confidence: 99%
See 2 more Smart Citations